Vestibular Schwannoma in the Only Hearing Ear: Role of Cochlear Implants. (February 2013) - Di Lella, Filippo; Merkus, Paul; Di Trapani, Giuseppe; Taibah, Abdelkader; Guida, Maurizio; Sanna, Mario
Objectives: We sought to delineate the role of cochlear implantation in the management of vestibular schwannoma or other cerebellopontine angle tumors in the only hearing ear. Methods: We performed a retrospective analysis in a quaternary referral skull base center of all patients who were affected by vestibular schwannoma (or other lesions of the cerebellopontine angle) in the only hearing ear and received a cochlear implant before or after tumor treatment (surgery or radiotherapy) or during the wait-and-scan follow-up. We also performed a systematic review of the English-language literature. Results: The clinical and audiological results of 10 patients are reported. All patients were managed with contralateral cochlear implantation. In 7 patients, cochlear implantation was performed before tumor removal, while hearing in the ear with the tumor was still present. In 3 patients, the implant was placed after curative surgery. Nine of the 10 patients routinely use their implant with subjective benefit and fairly good auditory performance (median disyllabic word recognition, 90%; median sentence comprehension, 75%). The literature search retrieved no major series with assessment of the long-term efficacy of cochlear implantation in this rare clinical scenario. Conclusions: Patients affected by vestibular schwannoma in their only hearing ear may significantly benefit from a cochlear implant on the contralateral side prior to tumor removal. Recent and significant hearing deterioration and tumor growth represent the main indications for cochlear implantation.